Microglia-Derived Extracellular Vesicles Carrying miR-711 Alleviate Neurodegeneration in a Murine Alzheimer’s Disease Model by Binding to Itpkb - Zhang, Yizhi; Xu, Chengbi; Nan, Yi; Nan, Shanji (Frontiers in Cell and Developmental Biology, 2020)
Neurodegeneration in Alzheimer's disease (AD) results in microglial activation, which may participate in the inflammatory cascade accelerating tissue damage. In this study, we sought to characterize the alleviatory role of miR-711 encapsulated in microglia-derived extracellular vesicles (EVs) in AD. Ultracentrifugation was employed to extract EVs from microglia (BV2 cells), which were identified using Western blot analysis of EVs marker proteins Alix and CD63. A repetitive mild traumatic brain injury (rmTBI) mouse model was induced by controlled cortical impact (CCI). After overexpressing miR-711 or Itpkb in BV2 cells, we evaluated the inflammation in BV2 cells and the ratio of microglia M2/M1. Further, we injected BV2 cell-secreted EVs with overexpressed miR-711 or Itpkb into rmTBI mice through the tail vein to investigate the inflammation in mouse serum, the ratio of microglia M2/M1 in brain tissue, and to evaluate neurological deficit and cognitive function. The EVs obtained by ultracentrifugation were successfully verified by Alix and CD63 expression. Mechanism studies suggest that miR-711 targeted Itpkb. By inhibiting Itpkb, miR-711 caould reduce the content of TNF-α and elevate the content of IL-10 in vivo and in vitro, repress Tau phosphorylation, and increase the ratio of M2/M1. Furthermore, miR-711-containing EVs reduced the score of neurological deficits and improved cognitive function in rmTBI mice. microglia-derived EVs loaded with miR-711, which mediates the hyperphosphorylation of Tau protein in the Itpkb pathway, effectively alleviating neurodegenerative changes and cognitive dysfunction in AD.